Status and Patients Satisfaction Attended at Emergency Department of a Tertiary Level Hospital in Dhaka City - Akhtar, Khursheda; Rashid, Md Mamun Or; Akhtar, Khodeza; Siddika, Ayesha; Siddika, Syeda Subrina (Journal of Current and Advance Medical Research, 2019)
Background: Emergency department is one of the most important parts of a hospital which is the point of major public health interest. Objective: The purpose of the present study was to find out the existing facilities of emergency department, to assess the satisfaction of patients and health care providers on emergency services. Method: This cross-sectional study was carried out at emergency department of Mugda Medical College, Dhaka, Bangladesh from January 2017 to June 2017 for a period of six (06) months. Research instruments were semi structured questionnaire. Existing facilities at emergency department were assessed by check list which was adopted from Table of Equipment (TOE) by Directorate General of Health Service (DGHS) and satisfaction level was categorized as good and bad. Face to face interview was taken from emergency patients and health care providers attending in emergency unit. Result: A total of 75 samples of respondents were selected purposively. Most of the respondents (30.0%) were in 26 to 35 years age group. According to their education level, 24(48.0%) were illiterate. Most of the respondents (76.0%) were attended to emergency unit by walking; however 48(96.0%) respondents attended by health care providers immediately. Half of the patients (50.0%) buy drugs from local dispensary and investigation in hospital was also done by half of the patients. After reaching at emergency, maximum patients 25(50.0%) waited for 1 to 5 minutes for receiving medical attention and mean waiting time was 10.14 minutes. Overall satisfactory level at emergency unit was good 23(46.0%) and bad 27(54.0%) (p<0.0001). Conclusion: Numbers of potential barriers influence the patients’ satisfaction. Periodic patient satisfaction survey should be institutionalized to provide feedback for continuous quality improvement. Journal of Current and Advance Medical Research 2019;6(1):53-58